Framing Terror of the Press: Pan & Kosicki's Model Analysis in TEMPO's Reporting on the Delivery of Pig Heads to the Tempo Office - Widyaningsih, Eni; Rahayu , Anisa (CV. Publikasi Indonesia, 2025)
The incident of sending a pig's head to the Tempo editorial office in March 2025 became a form of terror that marked press freedom in Indonesia. This study analyzes how Tempo frames the event using Pan & Kosicki's framing analysis model. The research method uses a qualitative approach with discourse analysis techniques on Tempo's headlines related to the event. The results of the study show that Tempo builds a narrative with an emphasis on Tempo's victimization, neutrality in the presentation of information, and strengthening democratic values through professional and measurable language. The framing used tends to support the position of journalists as victims and rejects all forms of intimidation against freedom of expression, where freedom of expression and opinion is enshrined in Law Number 40 of 1999 guarantees press freedom in articles 4, 5, 6 and 18 as human rights of citizens. Press freedom has norms or principles that measure the extent to which a country or community gives freedom to the media or press to carry out its role independently without unauthorized interference or intimidation or even threats of violence from interested parties. (President, 1999). Maintaining the media is the same as protecting the foundations of Indonesian democracy. (Suryaningsi et al., 2025).